Hydrothermal deglycosylation and deconstruction effect of steam explosion: Application to high-valued glycyrrhizic acid derivatives from liquorice. (1st March 2020) - Sui, Wenjie; Zhou, Mengjia; Xu, Yi; Wang, Guanhua; Zhao, Huan; Lv, Xiaoling
Highlights: There are hydrothermal deglycosylation of GL in SE process. Hydrolytic pathways consisted of complex consecutive and parallel reactions. Hydrolytic reactions were endothermic and non-spontaneous with entropy decreasing. SE removed structural components and restructured porous network of liquorice. Diffusion rate of GL and its hydrolyzed products was accelerated by SE. Abstract: In this work, steam explosion (SE) was exploited as a green and facile process to deconstruct liquorice's structure and deglycosylate glycyrrhizic acid (GL) to improve conversion and diffusion efficacy of GL and its hydrolyzed products. Results showed SE induced auto-hydrolysis of GL into glycyrrhetic acid 3-O-mono- β -D-glucuronide (GAMG) and glycyrrhetinic acid (GA), by which 30.71% of GL conversion, 5.24% and 21.47% of GAMG and GA formation were obtained. GL hydrolytic pathways were revealed by reaction kinetics and thermodynamics, which possessed complex consecutive and parallel reactions with endothermic, non-spontaneous and entropy-decreasing features. SE referred to cause cleavage of the β -1, 3 glycosidic bond in GL which was hydrolyzed to GA as a main product and GAMG and glucuronic acids as minor products. Diffusion of hydrolyzed products was accelerated by raising the diffusion coefficient and shortening the equilibrium time by over 90%. This work provides a sustainable and efficient route for product conversion and function enhancement of bioactive components.